A kind of anticrust acid and alkali corrosion resistant refractory coating for cement kiln flue and its preparation method

CN118955157BActive Publication Date: 2026-10-27HUZHOU CHANGXING XINGYING NEW TYPE REFRACTORY CONSTR MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411173202.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-26
Publication Date
2026-10-27
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

[0006]本发明是为了克服现有技术中耐火喷涂料难以适应水泥窑烟室环境,施工输送困难,耐磨性不佳,抗结皮和抗腐蚀性能差的缺陷,提供了一种水泥窑烟室用抗结皮耐酸碱腐蚀耐火喷涂料以克服上述缺陷

Benefits of technology

(1)本发明通过调整喷涂料中的含硅量,提高了喷涂料的耐酸碱性;并且使用柠檬酸钙和醚基聚羧酸酯作为分散剂,提高了在骨料粒径较小的情况下喷涂料的抗结皮性能;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application belongs to the technical field of refractory materials, and particularly relates to a cement kiln flue anti-skinning acid and alkali corrosion resistant refractory spray material and a preparation method thereof. The cement kiln flue anti-skinning acid and alkali corrosion resistant refractory spray material comprises, in percentage by weight, 50%-70% of aggregate, 20%-42% of micro powder, 3%-5% of binder, 1%-2.7% of expanding agent, 2%-3% of antioxidant, 0.1%-0.5% of anti-explosion agent, 0.1%-0.5% of anti-skinning agent and 0.15%-0.2% of dispersing agent. The maximum particle size of the aggregate is less than or equal to 3 mm. The dispersing agent comprises calcium citrate and ether-based polycarboxylate, and the mass ratio of the two is 1: (6-9). Compared with the traditional refractory spray material, the cement kiln flue anti-skinning acid and alkali corrosion resistant refractory spray material has high high-temperature compression strength, good wear resistance and shock resistance, strong acid and alkali corrosion resistance, good anti-skinning ability, excellent construction performance and better adaptability to complex working conditions in the flue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of refractory materials technology, specifically relating to an anti-scabbing and acid / alkali corrosion refractory spray coating for cement kiln smoke chambers and its preparation method. Background Technology

[0002] The smoke chamber of a cement kiln is a crucial component in the cement production process. Located between the preheater and the rotary kiln, it collects the high-temperature flue gas exiting the rotary kiln. Due to the extremely harsh working environment of the smoke chamber, including high temperatures, dust, chemical corrosion, and thermal shock, the requirements for refractory materials are very stringent. In the construction of new dry-process cement kilns, some parts, such as the smoke chamber, are currently still constructed using castable refractory materials. Casting requires the erection of formwork, resulting in a long construction period. The development and application of high-performance refractory spray coatings is one of the important development trends in cement kiln refractory engineering technology. Spray coatings can replace bricks and castable refractory materials in many applications, eliminating the need for on-site formwork. They offer convenient, simple, and rapid construction, short curing time, and short kiln drying cycles, saving significant time and accelerating equipment turnover and utilization.

[0003] The composition of refractory spray coatings is basically similar to that of similar refractory castables. The difference lies in the smaller critical particle size of the refractory aggregates in the spray coating, which is between 3mm and 5mm. Selecting aggregates with smaller critical particle sizes increases the surface area in contact with the binder, helping to improve the bonding strength of the spray coating. Furthermore, finer aggregates pass through the spray gun more easily, resulting in more uniform spraying and a denser coating, better meeting the transport requirements of spraying. However, the denser structure of the coating formed by fine aggregates may hinder the escape of internal moisture, leading to rapid evaporation of surface moisture while internal moisture evaporates more slowly, thus promoting skin formation. Additionally, to maintain the fluidity of the coating, coatings formulated with fine aggregates may require more binder. The binder is also more prone to skin formation during the drying process. Moreover, the relatively large specific surface area of ​​fine aggregates makes them more susceptible to chemical reactions, requiring stronger resistance to chemical erosion when used in smoke chambers.

[0004] The technical solution in patent CN202211454191.X includes 30-40 parts of 1-3mm cordierite, 28-38 parts of 0-1mm mullite, 10-15 parts of SiO2 micro powder, 5-11 parts of α-Al2O3 micro powder, 6-10 parts of fused calcium aluminate cement fine powder, 1-3 parts of additives, 0.2-0.8 parts of explosion-proof agent, and 5-10 parts of binder. The spray coating produced by this solution features good wear resistance, high fire resistance temperature, and excellent thermal shock resistance. It requires no formwork support during use, has a short construction period, low cost, and is easy to apply.

[0005] However, this design uses aggregates with small particle sizes, resulting in poor anti-scaling properties. Furthermore, its use in smoke chambers exposes the refractory materials to acidic gases that may corrode them. Additionally, the coating material has poor permeability; at high temperatures, moisture and gases within the coating cannot escape, potentially increasing internal pressure and thus raising the risk of cracking. Summary of the Invention

[0006] The present invention aims to overcome the shortcomings of existing refractory spray coatings, such as difficulty in adapting to the environment of cement kiln smoke chambers, difficulties in construction and transportation, poor wear resistance, and poor anti-scaling and anti-corrosion properties. It provides a refractory spray coating for cement kiln smoke chambers that is anti-scaling and resistant to acid and alkali corrosion to overcome the above-mentioned defects.

[0007] To achieve the objectives of the invention described above, the present invention is implemented through the following technical solution: A refractory spray coating for cement kiln flue chambers, resistant to scaling, acid and alkali corrosion, comprises, by weight percentage: 50%-70% aggregate, 20%-42% micro powder, 3%-5% binder, 1%-2.7% expanding agent, 2%-3% antioxidant, 0.1%-0.5% explosion retardant, 0.1%-0.5% anti-scaling agent, and 0.15%-0.2% dispersant; wherein the maximum particle size of the aggregate is ≤3mm, and the dispersant comprises calcium citrate and ether-based polycarboxylate in a mass ratio of 1:(6-9).

[0008] The cement kiln flue is located between the preheater and the rotary kiln, and is responsible for collecting the high-temperature flue gas from the rotary kiln. Because the working environment of the flue is extremely harsh, including high temperatures, dust, chemical corrosion, and thermal shock, the requirements for refractory materials are very stringent. They must ensure sufficient heat and wear resistance, as well as resistance to chemical corrosion, and should be as easy to construct, quick to install, and convenient for routine maintenance and replacement.

[0009] Refractory aggregates in refractory spray coatings typically employ multi-stage particle size ratios. Generally, spray coatings with smaller critical particle sizes pass more easily through the spray gun, resulting in more uniform spraying during application and promoting the formation of a dense coating, thus better meeting the conveying requirements of spray coating operations. However, overly dense spray coatings are more prone to cracking at high temperatures, and fine aggregates with larger specific surface areas are more likely to undergo oxidation-reduction reactions on their surfaces, affecting the overall performance of the spray coating.

[0010] The dispersant in this invention includes ether-based polycarboxylate and calcium citrate. Ether-based polycarboxylate is a polymer formed by grafting polyethylene glycol side chains onto an anionic backbone. It can adsorb onto the surface of negatively charged silica particles, forming a dense adsorption layer on the particle surface. This effectively reduces the surface energy between particles, thereby reducing mutual attraction and agglomeration. Through electrostatic interaction and the effect of non-adsorbent side chains, this anti-flocculation effect is very significant, allowing for uniform dispersion of the components in the spray coating, facilitating application, and improving the strength and durability of the coating. However, experiments have shown that the dispersion effect of ether-based polycarboxylate is limited in mixtures with excessively high micron content. Practical experience has shown that adding calcium citrate to spray coatings containing ether-based polycarboxylate further improves the fluidity of the coating and effectively slows down the hardening rate of cement or adhesives. When the mass ratio of calcium citrate to ether-based polycarboxylate is between 1:6 and 1:9, the coating exhibits better adhesion. Furthermore, calcium citrate decomposes at high temperatures, releasing gases that help the coating expand. This volume effect offsets some of the volume shrinkage, improving the material's high-temperature strength. On the other hand, it helps the coating generate microcracks at high temperatures, preventing the coating from cracking and simultaneously enhancing the material's resistance to acid and alkali corrosion and its resistance to skinning.

[0011] Preferably, the micro-powder is Al2O3 ultrafine powder and SiO2 ultrafine powder, with a mass ratio of 1:(3-5). Adding ultrafine powder serves two purposes: firstly, it fills the gaps between aggregate particles, forming a denser coating structure, reducing porosity, and improving the overall performance of the coating; secondly, it increases the SiO2 content, enhancing resistance to acidic and alkaline substances, thereby improving the coating's resistance to chemical corrosion.

[0012] Preferably, the aggregate is low-alumina mullite with a SiO2 content of 49%-55%. Using high-silicon, low-alumina, alkali-resistant raw materials as aggregate allows the high-silicon, low-alumina components to react with alkaline gases during use, generating a high-viscosity liquid phase that prevents alkali corrosion. Furthermore, the high-silicon aggregate also exhibits strong resistance to acidic environments.

[0013] Preferably, the SiO2 content in the spray coating is controlled to be above 40%.

[0014] As a preferred option, 2%-5% silicon carbide can also be added to the spray coating. Silicon carbide possesses high-temperature stability, which can improve the high-temperature performance, abrasion resistance, and corrosion resistance of the coating.

[0015] Preferably, the antioxidant comprises one or more of aluminum powder, aluminum silicate, and aluminum phosphate. Metallic aluminum powder is a commonly used antioxidant; it preferentially reacts with oxygen, protecting the presence of carbon, and the resulting product is also a high-melting-point substance.

[0016] Preferably, the explosion-proof agent is polypropylene explosion-proof fiber that melts at temperatures above 110°C. Using low-temperature, instant-melting explosion-proof fiber, during baking, the fiber's moisture-wicking reinforcement at a lower temperature prevents material cracking. At temperatures above 110°C, the fiber melts and oxidizes, creating pores that, in combination with calcium citrate, form microcracks. Water vapor can escape along these pores, releasing and relieving internal thermal stress, reducing material cracking, and improving the material's crack resistance. When the material experiences rapid heating or cooling, silicon carbide's high-temperature stability prevents the microcracks from extending and spreading, forming a network of microcracks. These microcracks absorb thermal stress, improving the material's thermal shock resistance.

[0017] Preferably, the binder is Guangxi white clay. Guangxi white clay has good chemical stability, does not easily react with acids or alkalis, and can improve the fluidity and workability of the mixture, making the spray coating easier to form and apply.

[0018] Preferably, the anti-skinning agent is one or a combination of two of calcium stearate and hydrogen-terminated polyether modified silicone oil. Calcium stearate (C36H70CaO4) is commonly used in lubricants; adding a small amount to spray coatings can form a protective film on the coating surface, preventing oxygen contact. Hydrogen-terminated polyether modified silicone oil (… H ( CH 2 CH 2 O ) nSi ( AND 3)3) is a type of polyether-modified silicone oil. It has good durability. Adding a small amount to spray paint can reduce the surface tension of the paint and prevent skinning caused by moisture evaporation.

[0019] A method for preparing an anti-scabbing, acid and alkali corrosion resistant spray coating for cement kiln smoke chambers, characterized by comprising the following steps in sequence: S1. Add aggregates, micro powders, binders, expanding agents, antioxidants, anti-explosion agents, anti-skinning agents, and dispersants, as well as water, to the mixer; S2. Turn on the mixer at a speed of 60-120 r / min and mix for 10-15 minutes to obtain the final spray coating.

[0020] Therefore, the present invention has the following beneficial effects: (1) The present invention improves the acid and alkali resistance of the spray coating by adjusting the silicon content in the spray coating; and improves the anti-skinning performance of the spray coating when the aggregate particle size is small by using calcium citrate and ether-based polycarboxylate as dispersants. (2) The present invention, through the combination of the explosion retardant and silicon carbide in the preferred scheme, forms microcracks on the surface of the spray coating, which effectively improves the explosion retardant performance of the spray coating.

[0021] (3) The present invention has good construction performance and low cost, which is conducive to its promotion and application in production practice. Detailed Implementation

[0022] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0023] Example 1 A refractory spray coating for cement kiln smoke chambers, resistant to scaling, acid and alkali corrosion, comprises, by weight percentage: 50% of the aggregate is made of low-alumina mullite, with a SiO2 content of 49% and a maximum aggregate particle size of ≤3mm. 42% micro powder, including 7% Al2O3 ultrafine powder and 35% SiO2 ultrafine powder; 3% binder, which is Guangxi white clay; 2.65% of the expanding agent is kyanite; 2% antioxidant, in the form of aluminum powder; 0.1% explosion-proof agent, which is polypropylene explosion-proof fiber melted at above 110℃; 0.1% of the anti-skinning agent is calcium stearate; 0.15% dispersant, which includes 0.02% calcium citrate and 0.13% ether-based polycarboxylate.

[0024] Add the above-mentioned aggregates, micro powders, binders, expanding agents, antioxidants, anti-explosion agents, anti-skinning agents, and dispersants, along with water equivalent to 30% of the total mass, to a mixer. Start the mixer at a speed of 60 r / min and mix for 10 minutes to obtain the final spray coating.

[0025] Example 2 A refractory spray coating for cement kiln smoke chambers, resistant to scaling, acid and alkali corrosion, comprises, by weight percentage: 60% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 32% micro powder, including 8% Al2O3 ultrafine powder and 24% SiO2 ultrafine powder; 3% binder, which is Guangxi white clay; 2.1% of the expanding agent is kyanite; 2% antioxidants, including 1% aluminum powder and 1% aluminum silicate; 0.25% explosion-proof agent, which is polypropylene explosion-proof fiber melted at above 110℃; 0.5% of the anti-skinning agent consists of 0.25% calcium stearate and 0.25% hydrogen-terminated polyether modified silicone oil; 0.15% dispersant, which includes 0.02% calcium citrate and 0.13% ether-based polycarboxylate.

[0026] Add the above-mentioned aggregates, micro powders, binders, expanding agents, antioxidants, explosion-proof agents, anti-skinning agents, and dispersants, along with water equivalent to 30% of the total mass, to a mixer. Start the mixer at a speed of 80 r / min and mix for 12 minutes to obtain the final spray coating.

[0027] Example 3 A refractory spray coating for cement kiln smoke chambers, resistant to scaling, acid and alkali corrosion, comprises, by weight percentage: 70% of the aggregate is made of low-alumina mullite, with a SiO2 content of 50% and a maximum aggregate particle size of ≤2mm. 20% micro powder, including 4% Al2O3 ultrafine powder and 16% SiO2 ultrafine powder; 5% binder, which is Guangxi white clay; The expanding agent is 1.1% kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% anti-skinning agent, which is hydrogen-terminated polyether modified silicone oil; 0.2% dispersant, which includes 0.02% calcium citrate and 0.18% ether-based polycarboxylate.

[0028] Add the above-mentioned aggregates, micro powders, binders, expanding agents, antioxidants, anti-explosion agents, anti-skinning agents, and dispersants, along with water equivalent to 30% of the total mass, to a mixer. Start the mixer at a speed of 120 r / min and mix for 15 minutes to obtain the final spray coating.

[0029] Example 4 A refractory spray coating for cement kiln smoke chambers, resistant to scaling, acid and alkali corrosion, comprises, by weight percentage: 65% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 26% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 2% silicon carbide; 4.1% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.2% dispersant, which includes 0.02% calcium citrate and 0.18% ether-based polycarboxylate.

[0030] Add the above-mentioned aggregates, micro powders, binders, expanding agents, antioxidants, anti-explosion agents, anti-skinning agents, and dispersants, along with water equivalent to 30% of the total mass, to a mixer. Start the mixer at a speed of 120 r / min and mix for 15 minutes to obtain the final spray coating.

[0031] Example 5 A refractory spray coating for cement kiln smoke chambers, resistant to scaling, acid and alkali corrosion, comprises, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.1% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.2% dispersant, which includes 0.02% calcium citrate and 0.18% ether-based polycarboxylate.

[0032] Add the above-mentioned aggregates, micro powders, binders, expanding agents, antioxidants, explosion-proof agents, anti-skinning agents, silicon carbide, and dispersants, along with water equivalent to 30% of the total mass, to a mixer. Start the mixer at a speed of 120 r / min and mix for 15 minutes to obtain the final spray coating.

[0033] To verify the effects of the selection of raw materials and the use of dispersants on the performance of the spray coating, the following comparative experiments were conducted. The preparation methods of the spray coatings in each comparative example were all in accordance with the preparation method of Example 5, and will not be repeated here.

[0034] Comparative Example 1 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55%, and the maximum particle size of the aggregate is between 5mm and 3mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.3% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; Comparative Example 2 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of mullite, with SiO2 content of 28%-30% and Al2O3 content of 70%-72%, and the maximum particle size of the aggregate is ≤2mm; 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.3% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; Comparative Example 3 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.3% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; Comparative Example 4 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.1% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.2% of the dispersant is an ether-based polycarboxylic acid ester.

[0035] Comparative Example 5 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.2% binder, which is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.1% dispersant, which includes 0.01% calcium citrate and 0.09% ether-based polycarboxylate.

[0036] Comparative Example 6 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 3.9% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.4% dispersant, which includes 0.04% calcium citrate and 0.36% ether-based polycarboxylate.

[0037] Comparative Example 7 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.1% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.2% dispersant, which includes 0.1% calcium citrate and 0.1% ether-based polycarboxylate.

[0038] Comparative Example 8 A refractory spray coating, comprising, by weight percentage: 62% of the aggregate is made of low-alumina mullite, with a SiO2 content of 55% and a maximum aggregate particle size of ≤2mm. 29% micro powder, including 4% Al2O3 ultrafine powder and 20% SiO2 ultrafine powder, and 5% silicon carbide; 4.1% of the binder is Guangxi white clay; The 1% expanding agent is kyanite; 3% antioxidants, including 1% aluminum powder, 1% aluminum silicate and 1% aluminum phosphate; 0.5% explosion-proof agent, which is polypropylene explosion-proof fiber that melts at temperatures above 110℃; 0.2% of the anti-skinning agent consists of 0.1% calcium stearate and 0.1% hydrogen-terminated polyether modified silicone oil; 0.2% dispersant, which includes 0.02% sodium citrate and 0.18% ether-based polycarboxylate.

[0039] Physical properties were tested according to GB / T4513.6-2017, acid resistance was tested according to GB / T17601-2008, and alkali resistance was tested according to GB / T 14983-2008. Table 1 shows the performance test results for Examples 1-5. Table 2 shows the performance test results for Comparative Examples 1-8. As shown in Tables 1 and 2 above, the spray coatings in Examples 1-5 of this invention exhibit significant advantages in terms of compressive strength, acid resistance, alkali resistance, and permanent linear change upon heating. Compared to Comparative Example 1, the coating structure in the spray coating with a larger critical aggregate particle size is looser. Although theoretically more wear-resistant, it is more prone to peeling at high temperatures and more susceptible to acid and alkali corrosion due to construction issues. Compared to Comparative Example 2, the high-alumina, low-silica spray coating has a larger mass, making it difficult to form a uniform coating, and its alkali resistance is significantly reduced. Compared to Comparative Example 3, without the addition of a dispersant, the spray coating has poor fluidity, and the higher content of powder will agglomerate, affecting construction and the overall performance of the spray coating. Compared to Comparative Example 4, when the dispersant ether-based polycarboxylate is added, the dispersion effect is not obvious due to the excessively high content of micropowder in the spray coating. Compared to Comparative Example 5, when the content of calcium citrate and ether-based polycarboxylate dispersant is too low, although the overall performance of the spray coating, especially its acid and alkali resistance, is improved, it does not reach the performance of the examples. Compared to Comparative Example 6, excessive addition of dispersant led to easy dilution of the spray coating, resulting in more pores within the coating and reducing its density, thus affecting its refractory performance and corrosion resistance. Compared to Comparative Example 7, excessive addition of calcium citrate reduced the dispersing effect of the dispersant, and at high temperatures, the excess calcium citrate decomposed and expanded, enlarging microcracks on the coating surface and affecting the compressive strength of the spray coating at high temperatures. Compared to Comparative Example 8, sodium citrate, a commonly used dispersant in monolithic refractories, has poor acid and alkali resistance. When used in refractory spray coatings, it is more easily destroyed by acid and alkali gases in the smoke chamber at high temperatures, resulting in spray coatings with poor compressive strength and anti-skinning properties.

Claims

1. A refractory spray coating for cement kiln smoke chambers that is resistant to scaling, acid and alkali corrosion, and characterized in that: Based on weight percentage, it consists of 50%-70% aggregate, 20%-42% micro powder, 3%-5% binder, 1%-2.7% expansion agent, 2%-3% antioxidant, 0.1%-0.5% explosion retardant, 0.1%-0.5% anti-skinning agent, and 0.15%-0.2% dispersant, totaling 100%. The maximum particle size of the aggregate is ≤3mm, and the dispersant includes calcium citrate and ether-based polycarboxylic acid ester, with a mass ratio of 1:(6-9). The micro powder is Al2O3 ultrafine powder and SiO2 ultrafine powder, and the mass ratio of the two is 1:(3-5). The aggregate is low-alumina mullite, with a SiO2 content of 49%-55%. The SiO2 content in the spray coating is ≥40%; The antioxidant includes one or more of aluminum powder, aluminum silicate, and aluminum phosphate; The explosion-proof agent is polypropylene explosion-proof fiber that melts at temperatures above 110°C; The binder is Guangxi white clay; The anti-skinning agent is one or a combination of two of calcium stearate and hydrogen-terminated polyether modified silicone oil.

2. The anti-scabbing, acid and alkali corrosion resistant spray coating for cement kiln flues according to claim 1, characterized in that: The micro powder also includes 2%-5% silicon carbide.

3. A method for preparing an anti-scabbing, acid and alkali corrosion resistant spray coating for cement kiln flues according to any one of claims 1-2, characterized in that: The steps are as follows: S1. Add aggregates, micro powders, binders, expanding agents, antioxidants, anti-explosion agents, anti-skinning agents, and dispersants, as well as water, to the mixer; S2. Turn on the mixer at a speed of 60-120 r / min and mix for 10-15 minutes to obtain the final spray coating.

Citation Information

Patent Citations

  • Cordierite-mullite spray coating and preparation method thereof

    CN115745633A

  • Silicon carbide anti-skinning fire-resistant spray paint

    CN103664204A